Development and Calibration of an Integrated Thin Ring Drawbar Pull Transducer for Agricultural Tractor (University of Khartoum Engineering Journal, 2022)
The objective of this research work is to design, develop and calibrate an integrated thin ring drawbar transducer for measuring the horizontal drawbar pull of agricultural tractor. The transducer is based on a thin proof ring that forms an integral part of the drawbar element with strain gauges bonded on the inside and the outside curvature of the proof ring. The strain gauges are arranged in a full bridge constant voltage circuitry and interfaced to a data acquisition system. Static calibration tests on the transducer showed high degree of linearity between applied load and output voltage with a coefficient of correlation (R2) equal to 0.9968. The transducer measurement accuracy was within the acceptable range limits with measurement errors not more than 0.67% of the measured force magnitudes under the static measurements. The data acquisition system was able to successfully scan and record the transducer signals as programmed. The developed transducer can be part of a complete instrumentation system to be used for developing comprehensive information database on power and energy demands of various tractors and implement field operations in Sudan.